Implementación y evaluación de sistema hidro-generador eléctrico, para el acueducto Veredal Vancouver - La Rambla del municipio de San Antonio del Tequendama (2022)
This project consists of the implementation of a micro generator that takes advantage of the water resources of the area in the Vancouver village in the Municipality of San Antonio del Tequendama, Cundinamarca. For its execution, several meetings were held with the project director Ing. Hugo Alba and the engineers Ávila Garzón Miguel Ángel, Gómez Cortés Hancel Raúl because they were in charge of advancing the design and development of the hydro generator system in its first phase. This project aims to supply electricity to future water purification equipment that the Veredal Vancouver La Rambla aqueduct intends to install. This Aqueduct collects water from the Quebrada Grande in the municipality of San Antonio del Tequendama. The implementation includes from the construction of the bench where the equipment is housed, the installation of the same, the pipe connections and water conduction hose, startup of the hydro generator and monitoring, the latter contains an alarm system in time due to faults in parameters such as delivered power, Pelton wheel RPM and flow rate. The relevant tests were carried out to determine compliance with the stipulated objectives. The main purpose of this project is to be able to cooperate in the well-being of the community of Veredas Vancouver and the Rambla of the municipality of San Antonio del Tequendama, which will benefit greatly from the implementation of this hydro generator in order to have the installation of equipment in the future. for purification.